LIBERALISASI PERDAGANGAN INTERNASIONAL DALAM PERSPEKTIF HUKUM ISLAM - Abdul Kholiq, Abdullah; Indriastuti, Suyani; Fathoni, Joharul (Universitas KH. MUkhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2024)
International trade is a process of exchange that is based on the voluntary will of each country. The motive is to obtain trade benefits or gains off trade. Trade is a very important economic activity today, so there are no countries in the world that are not involved in trade, whether inter-regional, inter-regional or inter-country trade. Trade liberalization or free trade is a condition where a country carries out trade between countries without any obstacles. This research is a qualitative descriptive study using literature. Based on the study above, it can be concluded that the perspective of Islamic law regarding international trade liberation is a liberal economic system that will give rise to social inequality and can endanger economic security stability which is in accordance with the Islamic concept which is based on the principles of justice, honesty, recognition of performance and hard work, humanism, and non-centralized.